Psychosocial determinants of functional independence among older adults: A systematic review and meta-analysis - Fataneh Goodarzi; Sahar Khoshravesh; Erfan Ayubi; Saeid Bashirian; Majid Barati (Tabriz University of Medical Sciences, 2024)
Background: In current years, the increase in older population has led to creating one of the main public health challenges, worldwide. Because of the special characteristics of older adults, this age group is exposed to possible problems, such as mental and physical disorders, that usually affect their functional independence. The study aimed to determine the psychosocial determinants (e.g., depression, social support, and self-efficacy) affecting functional independence among older population. Methods: Our search was conducted on three international databases (Web of Sciences, PubMed/Medline, and Scopus) for all the observational studies (cross-sectional, cohort or longitudinal designs) on the social and psychological determinants of functional independence among older adults. Papers published in English without limitation of time were reviewed from inception to 26 August 2023. The quality assessment tool was the Newcastle-Ottawa Scale (NOS). The I2 index was used to quantify the degree of heterogeneity among the studies. In the case of heterogeneity higher than 50%, the random effects model has been used for overall estimation of the effects; otherwise, the fixed effects model was used. The pooled associations were expressed as odds ratio (OR) and 95% confidence intervals (CIs). Stata version 14 software (StataCorp LP) was used for data analysis. The significance level was considered at 0.05. Results: In the initial search, 6978 articles were retrieved, and finally, considering the inclusion criteria, 46 articles were examined. Finally, 18 articles were eligible for meta-analysis. The findings indicated that among all the determinants affecting functional independence among older adults, depression could lead to a 76% increase in functional dependence. Conclusion: The findings provide a statistically significant relationship between psychosocial factors and functional independence. Depression was the strongest determinant of functional dependence among older adults.